2021
DOI: 10.1111/jdv.17232
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab for the treatment of recalcitrant eosinophilic dermatosis of haematologic malignancy

Abstract: Mason KJ, Burden AD, Barker JNWN et al. Risks of basal cell and squamous cell carcinoma in psoriasis patients after treatment with biologic vs non-biologic systemic therapies: results from the BADBIR, 2021. (submitted to JEADV). 2 George R, Weightman W, Russ GR et al. Acitretin for chemoprevention of non-melanoma skin cancers in renal transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In two of the reported patients, strikingly, no eosinophilia was found in the blood. All four patients reported rapid complete clearance of skin manifestations within 4–6 weeks ( Table 7 ) [ 8 , 218 , 219 , 220 ].…”
Section: Resultsmentioning
confidence: 99%
“…In two of the reported patients, strikingly, no eosinophilia was found in the blood. All four patients reported rapid complete clearance of skin manifestations within 4–6 weeks ( Table 7 ) [ 8 , 218 , 219 , 220 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our study found no excess of serum levels of IL-4 and IL-5, which play a role, respectively, in type 2 immune responses and eosinophil regulation (29), however, these interleukin levels were not tested in skin lesions, which is a limitation of the study. Few anecdotal reports of the use of monoclonal antibody blocking IL-4 and IL-13 (Dupilumab) in the treatment of EDHM show discordant outcomes that neither confirm nor contradict the possible role of IL-4 (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…However, this was the only result we found regarding cancer development during Dupilumab treatment (other than T-cell lymphomas, see section “Dupilumab and T-cell lymphomas”), so it is safe to say that this is most likely an isolated incident, with no link to the drug. Favorable outcomes have also been reported for patients with haematologic malignancy [ 26 , 27 , 28 ]. The results are summarized in Table 4 .…”
Section: Discussionmentioning
confidence: 99%